2014
DOI: 10.2151/sola.2014-018
|View full text |Cite
|
Sign up to set email alerts
|

Evolutions of Asian Summer Monsoon in the CMIP3 and CMIP5 Models

Abstract: The evolutions of Asian summer monsoon (ASM) are detected and evaluated based on the models in Couple Model Intercomparison Projects Phase-3 and Phase-5 (CMIP3 and CMIP5) for the 20 th Century climate simulation (20c3m and Historical runs, respectively). Considering that the individual models have various biases in rainfall amount simulation, instead of applying a fixed rainfall criterion as used in observation, we use model-dependent rainfall criteria to identify the simulated ASM onset, retreat, and duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Based on Tung et al . () and Kitoh et al . (), these results are consistent with the CMIP5 models’ overall performance in depicting the precipitation annual cycle within the EASM.…”
Section: Resultsmentioning
confidence: 94%
“…Based on Tung et al . () and Kitoh et al . (), these results are consistent with the CMIP5 models’ overall performance in depicting the precipitation annual cycle within the EASM.…”
Section: Resultsmentioning
confidence: 94%
“…region better than the CMIP3 models (Jourdain et al 2013) but have a dry bias in the early rainy season (Seth et al 2013). Tung et al (2014) noted a delayed onset of the South Asian summer monsoon by CMIP models compared with observations.…”
Section: Asian Monsoon a Aogcms (1) South Asian Monsoonmentioning
confidence: 82%
“…They found that the CMIP5 models better reproduce the Asian summer monsoon domain than the CMIP3 models both for hit rate and threat score. Tung et al (2014) also noted that models that use the hybrid convective parameterization, combining bulk mass flux and CAPE closure schemes, are better than models with other convection schemes. Hsu et al (2011) and Kitoh et al (2013) assessed the GMA and GMI of each model against observations.…”
Section: Global Monsoon a Observationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The present climate observation shows a steeper curve with MME (ALL), yet, it is comprised of the diffused 16 models. This may be caused by the coarse resolution and missing precipitation contributed by typhoons, Mei-Yu fronts and southwest flows of CGCMs (Stocker et al 2013;Tung et al 2014). However, the increase observation trend is higher than ALL even in the RCP45 and RCP85 experiments.…”
Section: Observed and Modeled Trendsmentioning
confidence: 96%